(untitled) (Revista Electrónica REDINE, 2018)
This research aims to generate reflections on vision with teachers on recreational sport in the university context; it is framed in the interpretative paradigm under a qualitative approach to the implementation of hermeneutical phenomenological method. For information the technique of semi-structured interview to social actors who are specialists in physical education and sport graduates of the Pedagogical University Experimental Libertador Pedagogical - Institute Pedagogical of Barquisimeto was applied. categories of analysis and the respective findings contained therein were used for organization and interpretation, and triangulation is also performed by categories of analysis and contextualization of all information. It is derived which should promote diversification of recreational sport in college for maintaining physical health of students, as well as strengthening the bonds of friendship through sport oriented education across the population, and consolidating entity other respects non-federated sports organizations, linking the university with communities; considering that these activities are in the process of self-agency support organization.